Upaya meningkatkan keterampilan Berpikir Kreatif dan Kolaboratif siswa SDN Kanorejo 2 (studi kasus menggunakan Fishbone Diagram) - Rahmawati, Ika; Dumiyati, Dumiyati; Supiyanto, Yudi (Borobudur Educational Review, 2025)
This research, entitled Efforts to Improve Students' Creative and Collaborative Thinking Skills at SDN Kanorejo 2 (case study using Fishbone Diagrams), aims to interpret efforts to improve students' critical and collaborative thinking skills. The research is qualitative research using fishbone diagrams. The research results show that efforts can be made to overcome solutions to 3 main problems, namely manpower, machine, and method. Barriers to learning at SDN Kanorejo 2 are (1) Learning technology has not been utilized optimally, (2) Low creative thinking ability of students, (3) Learning methods have not been varied, (4) Low cognitive ability of students, (5) Collaboration ability between students low. From these problems, researchers found solutions, namely (1) Creating interactive learning media, (2) Designing learning that requires students' creative thinking patterns, (3) Providing variations in teaching methods by combining various teaching methods, (4) Creating a fun learning environment, (5) Increasing project-based learning and problem-based learning methods.